2019
DOI: 10.1016/j.devcel.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent Cells Actively Replenish CENP-A Nucleosomes to Maintain Centromere Identity and Proliferative Potential

Abstract: Highlights d CENP-A nucleosomes are gradually incorporated in quiescent cells and oocytes d CENP-A deposition during quiescence is required for future chromosome segregation d RNA Polymerase transcription at centromeres promotes gradual CENP-A exchange d Terminally differentiated muscle cells fail to retain CENP-A nucleosomes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 45 publications
5
45
0
Order By: Relevance
“…We find that the predominant factor controlling alpha-satellite transcription is the presence of centromere-nucleolar contacts, providing a mechanism to modulate centromere transcription and chromatin dynamics across diverse cell states and conditions. Together, our results support a role for ongoing transcription in promoting the dynamics of centromeric chromatin (Swartz et al, 2019).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…We find that the predominant factor controlling alpha-satellite transcription is the presence of centromere-nucleolar contacts, providing a mechanism to modulate centromere transcription and chromatin dynamics across diverse cell states and conditions. Together, our results support a role for ongoing transcription in promoting the dynamics of centromeric chromatin (Swartz et al, 2019).…”
Section: Introductionsupporting
confidence: 71%
“…The nature of the behavior that we observed for alphasatellite smFISH foci, including the lack of localization to centromeres or mitotic structures, is inconsistent with a direct, physical role for these transcripts in cell division processes. Instead, this suggests a role for the transcription process itself, such as a role for ongoing transcription to promote the dynamics and rejuvenation of centromeric chromatin, as proposed by our recent work in non-dividing cells (Swartz et al, 2019).…”
Section: Nucleolar Associations Act To Repress Alpha-satellite Transcmentioning
confidence: 85%
“…This frequent mis-segregation suggested a more severe defect, perhaps due to active stripping of previously loaded CENP-A from the centromeres of bridge chromosomes. To address this possibility, we pulse-labeled cells expressing Halo-tagged CENP-A from its endogenous locus (55) prior to the induction of chromosome bridges, enabling preferential visualization of the preexisting population of CENP-A that was loaded prior to bridge formation. After labeling and bridge induction (TRF2-DN), cells were given sufficient time to divide twice—first to form bridges, and again to allow bridges to be converted to micronuclei (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that both Cid1 and Cid5 are present at centromeres early in oogenesis but only Cid1 remains on centromeres by meiosis I metaphase arrest. Given that turnover of CenH3-containing nucleosomes in MI-arrested oocytes appears to be quite gradual (~2% of centromeric CenH3 is exchanged per day in MI-arrested starfish oocytes (Swartz, Mckay et al 2018)), we hypothesize that Cid5 protein is actively removed from the oocyte centromeres and at the onset of meiosis I metaphase arrest. Since Cid1 is always present throughout oogenesis, it is unclear whether Cid5 performs any function, centromeric or otherwise, in the female germline.…”
Section: Differential Localization Of Cid1 and Cid5 In D Virilis Ovamentioning
confidence: 96%
“…Oocyte centromere function does not seem to depend on the loading of newly transcribed CenH3 as conditional knockouts of CenH3 in meiotic prophase I are fully fertile in Mus musculus (Smoak, Stein et al 2016). However, recent work demonstrated that CenH3 in MI arrested starfish oocytes undergoes gradual turnover, presumably to replace CenH3 containing nucleosomes that are disturbed by transcriptional machinery, allowing oocytes to maintain centromere competence over long periods of time (Swartz, Mckay et al 2018). This means that CenH3 molecules are capable of stably persisting in oocytes for long periods of time and that there are mechanisms in place to maintain centromere function in non-dividing cells.…”
Section: Introductionmentioning
confidence: 99%